Isotope Compositions of Century‐Long Corals Reveal Significant Dissolved Cu, Zn Fluxes From Human‐Accelerated Weathering Into the Ocean - Liu, Yi; Chen, Maoqing; Zhang, Ting; Zhang, Rui; Cao, Fei; Sun, Shaobo; Zheng, Wang; Sun, Ruoyu; Chen, Jiubin (Geophysical research letters, 2023)
Human activities have liberated substantial amounts of biologically active metals into oceans. However, identifying the sources and migration processes of these metals is challenging. Here we present first century‐long records of concentrations and isotope compositions of Zn and Cu (δ66Zn and δ65Cu) in two corals from the northern South China Sea. The results show dramatic enrichment in coral Zn and Cu concentrations since the 1980s, which coincide with δ66Zn and δ65Cu increases. Coupled with concurrent land use/cover changes, we suggest that the enrichment trends of Cu and Zn in corals are best explained by human‐induced rock weathering and soil erosion, which transferred isotopically heavy Zn and Cu fluxes into the coastal ocean. The metal releases due to land use/cover changes relative to direct anthropogenic sources could be even more significant in the future given that anthropogenic releases have been legally controlled and started to decline in recent decades. Plain Language Summary Substantial amounts of biologically active but potentially toxic metals such as zinc and copper have been released into the Earth's surface due to increasing human activities. Most previous studies linked marine zinc and copper enrichment to direct human‐related releases that are transferred into oceans via atmospheric deposition and river discharge, but neglected natural releases that have been augmented by human activities. Here, we found that zinc and copper levels in annually banded corals from South China Sea coastal areas are increasing since the early 1980s, and these increasing trends are best explained by human‐induced rock weathering and soil erosion based on evidence from first measured isotope signatures and land use/cover changes. This pathway was largely overlooked before, but might be a predominant pathway accounting for marine metal enrichment in future given more and more strict environmental laws targeted at curbing metal releases by human activities. Key Points The coral Zn and Cu isotopic compositions indicate progressive changes of Zn and Cu sources into the ocean through the time Unprecedented enrichment of coastal Zn and Cu since the 1980s is associated with increases in δ66Zn and δ65Cu Human‐induced rock weathering and soil erosion mainly contributed increased fluxes of dissolved Zn and Cu